SOSIALISASI PENERAPAN POLA HIDUP BERSIH DAN SEHAT DI SD DAN SMP DESA NGASINAN - Arifiani, Dian; Mahendra, Dimas Aji; Khoirunnisa, Haida; Ilmi, Indy Naelul; Hasanah, Uswatun (Universitas Sanata Dharma, 2023)
Health problems became the primary human need. Indonesia's health-care challenge is its low ability and willingness to adopt a clean, healthy pattern of living. People's lack of awareness of cleanliness will have adverse effects. This socialization aims to enhance the quality of student behavior and foster an awareness of the importance of a clean, healthy pattern of living in the school environment. PHBS is carried out in the form of socialization and a practice focused on Ngasinan primary school students and the Sudirman Susukan Islamic middle school, with secondary and seventh graders. The methods used in this study are qualitative methods and literature study analytics. PHBS application in the school will support the teaching process and learners will concentrate more on studying. KKN UIN Walisongo students teach students to wash their hands with soap before eating and teach their students how to wash their hands well and right. In addition, students of KKN also provide secondary students with education on the dangers of smoking and feeding elementary and junior high students a supplementation of carbohydrate, fat and protein and soy milk containing the content of vegetable fat, protein, calcium, minerals (thiamine, folate, riboflavin, potassium, magnesium, zinc and iron).